D-Meson azimuthal anisotropy in midcentral Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Physical review letters, 2018)
The azimuthal anisotropy coefficient v2 of prompt D0, D+, D*+, and D+s mesons was measured in midcentral (30%-50% centrality class) Pb-Pb collisions at a center-of-mass energy per nucleon pair √sNN=5.02 TeV, with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decays at midrapidity, |y|<0.8, in the transverse momentum interval 1<pT<24 GeV/c. The measured D-meson v2 has similar values as that of charged pions. The D+s v2, measured for the first time, is found to be compatible with that of nonstrange D mesons. The measurements are compared with theoretical calculations of charm-quark transport in a hydrodynamically expanding medium and have the potential to constrain medium parameters.